Photocatalyst-Free, Visible-Light-Mediated C–H Perfluoroalkylation of Quinazolin-4(3H)-ones with perfluoroalkyl Iodides - Delouche, Thomas; Gadiry-Diallo, Abdoul; Besson, Thierry; Ogoshi, Sensuke; Fruit, Corinne (Synthesis, 2023)
A practical and sustainable photocatalyst-free protocol for photoinduced synthesis of perfluoroalkylated quinazolin-4(3H)-ones is described starting from quinazolin-4(3H)-ones. A wide range of substituted or fused-quinazolinones is found to be compatible, providing the corresponding mono- and bis-perfluoroalkylated compounds in moderate yields. This visible-light-mediated C–H perfluoroalkylation allows an environmentally friendly and straightforward access to an array of unprecedented functionalized quinazolinone scaffolds, presenting attractive features for drug discovery. Control experiments demonstrated that a radical mechanism is involved in the reaction mechanism.
Keywords: visible light; perfluoroalkylation; quinazolin-4(3H)-ones; thiazoloquinazolinone; C–H functionalization; metal-free